ap-index solar wind driving function and its semiannual variations - A. A. Petrukovich; M. Y. Zakharov (Annales Geophysicae, 2007)
Semiannual variation of geomagnetic activity and ap-index in particular is supposed to consist of heliospheric factor (axial hypothesis and Russell-McPherron effect) and magnetospheric/ionospheric factor (equinoctical hypothesis). In our investigation we express ap-index as a magnetospheric response function to solar wind and IMF input. Seasonal variation in ap-index on average (1963–2003) is ~4 nT and consists of ~2.1–2.3 nT of magnetospheric/ionospheric part, 0.6–1.3 nT of heliospheric part (including 0.2–0.3 nT of R-M effect), 0.1–0.4 nT is due to the non-linear term. 90% confidence range of all estimates is ~0.1–0.25 nT. While autumn/spring magnetospheric response functions are almost identical, there is substantial difference between winter and summer functions. The increase of solar wind input in autumn and spring is also different by a factor of two.